Kesadaran Mahasiswa Pendidikan Geografi Pada Lingkungan - Nurul Hasanah; La Harudu; La Ode Amaluddin; La Ode Hadini (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Environmental protection begins with generating environmental awareness among the people. The source of all environmental problems is human activity to meet their needs without regard to the carrying capacity of the environment. This study aims to determine the environmental awareness of the Geography education students class of 2020 in the Faculty of Teacher Training and Education, Halu Oleo University. The research method used is descriptive quantitative through questionnaires to 30 students. The results showed that the majority of students majoring in Geography education class of 2020 had high environmental awareness in the Teaching and Education Faculty. Analysis of the three aspects of student awareness of the environment (knowledge, attitudes, and behavior) is in the high category with their respective percentages of 36.67%, 33.33%, and 36.67%.